Desaın Penerapan Cloud Technology Sebagaı Infrastruktur Kota: Case Study Kota Batam - Hendi Sama; Abizar Muhammad Lubis (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
In the development of cloud technology, it has many advantages compared to conventional systems. Cloud Technology is an online-based data storage and data sharing service that relies on the internet to organize and manage data. The solution to the problem of implementing a cloud based infrastructure in Batam is using the NDLC (Network Development Life Cycle) method which includes the stages of analysis, implementation, monitoring, simulation, design, and management. The result of this application qill be a Cloud based technology system which can build infrastructure in the city of Batam which is much better in terms of data sharing by using access rights so that only certain people have access to data which will ensure data security